Pemberdayaan Petani Melalui Penyuluhan dan Demonstrasi Pembuatan Pupuk Organik Cair (POC) dari Buah Busuk di Desa Itterung: Pengabdian - Andi Kasmawati; A.Muh. Anugrah; Nurkhalifa; A. Alyana; Novi; Aisyah Bahar; Nurul Aulia Ramadani; Arham Jaya; Muh. Ikbal (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The problem of post-harvest fruit waste and the rising cost of inorganic fertilizers pose challenges for farmers in Itterung Village. Extension activities and demonstrations of making liquid organic fertilizer (POC) from rotten fruit were carried out to improve farmers' knowledge and skills in utilizing local organic waste as a valuable cultivation input. The methods used included interactive lectures, group discussions, direct demonstrations (demonstration plots/DEMPLOT), and follow-up assistance. The main ingredients of POC are rotten fruit, sugar/molasses, fermented for 7–15 days. Indicators of success were measured through pre-post tests, practical observations, and technology adoption. The results of the activity showed an increase in participant knowledge (10% to 40%), the formation of a village POC working group, and initial production of approximately 2 liters of POC. A simple analysis showed the potential for fertilizer cost savings of up to 15% per planting season. This activity effectively reduced organic waste, reduced farming costs, and increased farmer capacity.